Genetic Analysis and Follow-Up of 25 Neonatal Diabetes Mellitus Patients in China - Bingyan Cao; Chunxiu Gong; Di Wu; Chaoxia Lu; Fang Liu; Xiaojing Liu; Yingxian Zhang; Yi Gu; Zhan Qi; Xiaoqiao Li; Min Liu; Wenjing Li; et al. (Journal of Diabetes Research)
Aims. To study the clinical features, genetic etiology, and the correlation between phenotype and genotype of neonatal diabetes mellitus (NDM) in Chinese patients. Methods. We reviewed the medical records of 25 NDM patients along with their follow-up details. Molecular genetic analysis was performed. We compared the HbA1c levels between PNDM group and infantile-onset T1DM patients. Results. Of 25 NDM patients, 18 (72.0%) were PNDM and 7 (28.0%) were TNDM. Among 18 PNDM cases, 6 (33.3%) had known KATP channel mutations (KATP-PNDM). There were six non-KATP mutations, five novel mutations, including INS, EIF2AK3 (n=2), GLIS3, and SLC19A2, one known EIF2AK3 mutation. There are two ABCC8 mutations in TNDM cases and one paternal UPD6q24. Five of the six KATP-PNDM patients were tried for glyburide transition, and 3 were successfully switched to glyburide. Mean HbA1c of PNDM was not significantly different from infantile onset T1DM (7.2% versus 7.4%, P=0.41). Conclusion. PNDM accounted for 72% of NDM patients. About one-third of PNDM and TNDM patients had KATP mutations. The genetic etiology could be determined in 50% of PNDM and 43% of TNDM cases. PNDM patients achieved good glycemic control with insulin or glyburide therapy. The etiology of NDM suggests polygenic inheritance.